Gastric cancer is associated with NOS2 -954G/C polymorphism and environmental factors in a Brazilian population - Jorge, Yvana C. [UNESP]; Duarte, Marcia C. [UNESP]; Silva, Ana E. [UNESP] (Springer Nature, 2010)
Background: Gastric cancer can progress from a chronic inflammation of the gastric mucosa resulting from Helicobacter pylori infection that activates the inflammatory response of the host. Therefore, polymorphisms in genes involved in the inflammatory response, such as inducible nitric oxide synthase (NOS2), have been implicated in gastric carcinogenesis. The aim of this study was to evaluate the association of NOS2 polymorphisms Ser608Leu (rs2297518) in exon 16, -954G/C and -1173C/T, both in the promoter region, with gastric cancer and chronic gastritis and the association of cancer with risk factors such as smoking, alcohol intake and H. pylori infection.Methods: We conducted a population-based case-control study in 474 Southeast Brazilian individuals (150 with gastric cancer, 160 with chronic gastritis, and 164 healthy individuals), in which we performed NOS2 genotyping by PCR-RFLP.Results: SNP Ser608Leu was not associated with risk of chronic gastritis or gastric cancer. The polymorphic allele -1173T was not found in the studied population. However, the frequency of -954GC+CC genotypes was significantly higher (p < 0.01) in the cancer group (48.7%) than in both the gastritis (28.1%) and the control (29.9%) groups. Multivariate logistic regression showed that the NOS2 SNP -954G/C was associated with higher risk of gastric cancer (OR = 1.87; 95% CI = 1.12-3.13). We also observed an association with risk factors such as smoking and alcohol intake in both the gastric cancer (OR = 2.68; 95% CI = 1.58-4.53; OR = 3.60; 95% CI = 2.05-6.32, respectively) and the chronic gastritis (OR = 1.93; 95% CI = 1.19-3.13; OR = 2.79; 95% CI = 1.55-5.02, respectively) groups. This is the first report of increased risk of gastric cancer in association with the -954G/C polymorphism. These findings show that several polymorphisms in the promoter region of the NOS2 gene may contribute to the susceptibility to gastric cancer.Conclusions: Polymorphism NOS2 -954 G/C, along with alcohol intake and tobacco smoking, is associated with gastric cancer. However, the NOS2 Ser608Leu polymorphism was not associated with gastric carcinogenesis. The NOS2 -1173C/T polymorphism was absent in the studied population. © 2010 Cristina et al; licensee BioMed Central Ltd.